2021
DOI: 10.3389/fimmu.2021.712948
|View full text |Cite
|
Sign up to set email alerts
|

High Na+ Environments Impair Phagocyte Oxidase-Dependent Antibacterial Activity of Neutrophils

Abstract: Infection and inflammation can augment local Na+ abundance. These increases in local Na+ levels boost proinflammatory and antimicrobial macrophage activity and can favor polarization of T cells towards a proinflammatory Th17 phenotype. Although neutrophils play an important role in fighting intruding invaders, the impact of increased Na+ on the antimicrobial activity of neutrophils remains elusive. Here we show that, in neutrophils, increases in Na+ (high salt, HS) impair the ability of human and murine neutro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 111 publications
(161 reference statements)
3
6
0
Order By: Relevance
“…The reasons underlying the discrepancy between our results and those reported by Hatanata and coworkers are not clear, since similar experimental conditions were used in both studies. On the other hand, and consistent with our observations, Krampert and coworkers (29) recently reported that high salt induced IL-8 production and boosted IL-8 production of neutrophils infected with E.coli. However, contrasting with our results, Krampert and coworkers observed that high salt boosted IL-8 production after a short incubation period, i.e., 1.5 h, time at which we observed a profound inhibition in the production of IL-8 triggered by LPS.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The reasons underlying the discrepancy between our results and those reported by Hatanata and coworkers are not clear, since similar experimental conditions were used in both studies. On the other hand, and consistent with our observations, Krampert and coworkers (29) recently reported that high salt induced IL-8 production and boosted IL-8 production of neutrophils infected with E.coli. However, contrasting with our results, Krampert and coworkers observed that high salt boosted IL-8 production after a short incubation period, i.e., 1.5 h, time at which we observed a profound inhibition in the production of IL-8 triggered by LPS.…”
Section: Discussionsupporting
confidence: 93%
“…However, contradictory observations have also been published. In fact, different studies have reported that high salt enhances (26) or suppresses neutrophil antibacterial activity (27)(28)(29). Similar contrasting findings have been reported regarding the ability of high salt to modulate the production of NETs (29,30) as well as the release of IL-8 by neutrophils (29,31).…”
Section: Introductionmentioning
confidence: 55%
See 1 more Smart Citation
“…Consistently, high NaCl can impaire the antimicrobial capacities of both human and murine neutrophils. In human neutrophils, the reduced bactericidal activity was due to the decreased reactive oxygen species (ROS) production 81 . Furthermore, an HSD in mice can increase the urea accumulation in the renal medulla and elevate the glucocorticoid level in the blood, resulting in the suppressed neutrophil antibacterial functionality.…”
Section: The Effect Of High Salt On Immune Cellsmentioning
confidence: 99%
“…In human neutrophils, the reduced bactericidal activity was due to the decreased reactive oxygen species (ROS) production. 81 Furthermore, an HSD in mice can increase the urea accumulation in the renal medulla and elevate the glucocorticoid level in the blood, resulting in the suppressed neutrophil antibacterial functionality. Healthy humans who accepted an HSD also showed hyperglucocorticoidism and inhibited neutrophil function.…”
Section: Neutrophilsmentioning
confidence: 99%